2008
DOI: 10.1093/jn/138.10.1923
|View full text |Cite
|
Sign up to set email alerts
|

A 9-cis β-Carotene–Enriched Diet Inhibits Atherogenesis and Fatty Liver Formation in LDL Receptor Knockout Mice

Abstract: Our aim was to study the effect of 9-cis beta-carotene-rich powder of the alga Dunaliella bardawil on lipid profile, atherogenesis, and liver steatosis in high-fat diet-fed LDL receptor knockout mice. In 4 sets of experiments, mice were distributed into the following groups: control, fed an unfortified diet; Dunaliella 50, fed a diet composed of 50% 9-cis and 50% all-trans beta-carotene; Dunaliella 25, fed a diet containing 25% 9-cis and 75% all-trans beta-carotene; beta-carotene-deficient Dunaliella, fed beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 36 publications
5
74
1
1
Order By: Relevance
“…β-Carotene supplementation could alleviate hepatic SS in HFD-fed mice [20]. β-Carotene is able to modulate the nuclear factor κB pathway and nuclear factor erythroid 2-related factor 2 pathway to inhibit downstream production of inflammatory cytokines and oxidative stress [21].…”
Section: Discussionmentioning
confidence: 99%
“…β-Carotene supplementation could alleviate hepatic SS in HFD-fed mice [20]. β-Carotene is able to modulate the nuclear factor κB pathway and nuclear factor erythroid 2-related factor 2 pathway to inhibit downstream production of inflammatory cytokines and oxidative stress [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although low concentrations are found in circulating human serum, cis-BC isomers are present in human tissues where it is thought that they exert their biological function(s) (Deming, Baker, & Erdman, 2002;Stahl & Sies, 1993). Recently, it has been suggested that cis-BC isomers may also have a role in preventing atherogenesis (Harari et al, 2008); however, studies are still ongoing to fully elucidate these findings.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies suggest that a diet rich in carotenoids is associated with a reduced risk of heart disease and cancer (Melendez-Martinez et al, 2004). Harari et al (2008) suggested that 9-cis b-carotene have the potential to inhibit atherogenesis in humans via its conversion to 9-cis retinoic atherogenic effect of the extract mixtures may be due to the presence of phenolic compounds, phytosterols, tocopherols and unsaturated fatty acids. The studied mixtures showed complete safety towards liver and kidney functions.…”
Section: Resultsmentioning
confidence: 99%